THE EFFECT OF GOVERNMENT EXPENDITURE ON INDONESIAN GROSS DOMESTIC REGIONAL BRUTO (2017-2019) - A Kusumaningrum (Jurnal Pendidikan Ekonomi Indonesia, 2022)
This study aims to determine the effect of government expenditure on gross regional domestic product in Indonesia. The data used is secondary data on government spending and PDRB which is taken through the Badan Pusat Statistika (BPS). Data is obtained from panel data from 34 provinces in Indonesia in 2017-2019. This study uses a common effect. The results of this study indicate that government spending has a positive and significant effect on GDRB (Gross Domestic Regional Bruto)